The effect of antibiotic exposure on eicosanoid generation from arachidonic acid and gene expression in a primitive chordate, Branchiostoma belcheri. Issue 1 (29th July 2015) - Yuan, Dongjuan; Pan, Minming; Zou, Qiuqiong; Chen, Chengyong; Chen, Shangwu; Xu, Anlong
Abstract : Chloramphenicol (Chl) is an effective antimicrobial agent widely used in veterinary medicine and commonly used in fish. Its use is restricted in the clinic because of adverse effects on the immune system and oxidative stress in mammals. However, the effects of Chl treatment on invertebrates remain unclear. Amphioxus, a basal chordate, is an ideal model to study the origin and evolution of the vertebrate immune system as it has a primary vertebrate‐like arachidonic acid (AA) metabolic system. Here, we combined transcriptomic and lipidomic approaches to investigate the immune system and observe the oxygenated metabolites of AA to address the antibiotic effects on amphioxus. Tissue necrosis of the gill slits occurred in the Chl‐treated amphioxus, but fewer epithelial cells were lost when treated with both Chl and ampicillin (Amp). The immune related pathways were dysregulated in both of the antibiotic treatment groups. The Chl alone treatment resulted in immunosuppression with down‐regulation of the innate immune genes. In contrast, the Chl + Amp treatment resulted in immunostimulation to some extent, as shown by KEGG clustering. Furthermore, Chl induced a 3‐fold reduction in the level of the eicosanoids, while the Chl + Amp treatment resulted in 1.7‐fold increase of eicosanoid level. Thus in amphioxus, Amp might relieve the effects of the Chl‐induced immune suppression and increase the level of eicosanoids from AA. Finally, the oxygenated metabolites from AA might be crucial to evaluate the effects of Chl treatment in animals. Abstract : Chloramphenicol treatment induced immunosuppression and severe tissue damage in amphioxus. KEGG clustering showed that chloramphenicol and ampicillin treatment resulted in immunostimulation. Chloramphenicol treatment induced a ∼3‐fold decrease of eicosanoid levels. Chloramphenicol and ampicillin treatment resulted in a 1.7‐fold increase of eicosanoid levels. Eicosanoids derived from arachidonic acid provide insights into the effect of chloramphenicol treatment.